2015
DOI: 10.1016/j.vaccine.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of functional influenza virus-specific CD8+ T cell memory pools after intramuscular immunization

Abstract: The emergence of the avian-origin influenza H7N9 virus and its pandemic potential has highlighted the ever-present need to develop vaccination approaches to induce cross-protective immunity. In this study, we examined the establishment of cross-reactive CD8(+) T cell immunity in mice following immunization with live A/Puerto Rico/8/1934 (PR8; H1N1) influenza virus via two non-productive inoculation routes. We found that immunization via the intramuscular (IM) route established functional influenza-virus specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, human studies on LAIV show minimal increases in CD8 + T cell responses after vaccination, as measured by IFNγ production [106,107]. Nevertheless, it remains unclear whether the poor results observed in these human LAIV trials are due to the fact that CD8 + T cells are being assessed within the peripheral blood, while memory T cell responses generated after LAIV in mice are established at the site of infection [108].…”
Section: Vaccine Strategies For Induction Of Broadly Cross-reactive Amentioning
confidence: 99%
“…However, human studies on LAIV show minimal increases in CD8 + T cell responses after vaccination, as measured by IFNγ production [106,107]. Nevertheless, it remains unclear whether the poor results observed in these human LAIV trials are due to the fact that CD8 + T cells are being assessed within the peripheral blood, while memory T cell responses generated after LAIV in mice are established at the site of infection [108].…”
Section: Vaccine Strategies For Induction Of Broadly Cross-reactive Amentioning
confidence: 99%
“…Infection with LAIV induces no or mild upper respiratory symptoms mimicking a subclinical influenza virus infection (Hoft et al, 2017). Viral infection activates both systemic and localized innate and adaptive immune responses, which provide protection by a variety of mechanisms including viral interference (Wang et al, 2015), antiviral NK cell activation at the site of infection (Laurie et al, 2015), influenza-specific cross-reactive T cell activation and expansion (Schultz-Cherry, 2015), generation of highavidity mucosal neutralizing sIgA antibody (Mohn et al, 2017) and induction of immunological memory to influenza virus antigens (van Riet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated the establishment of functional influenza- virus-specific CD8+ and CD4+ T cells after both intranasal and intramuscular immunization with IIV (Wang et al, 2015; Keijzer et al, 2014; Ann et al, 2014). It would therefore also be important to reconsider the genome composition of reassortant viruses for IIVs.…”
Section: Discussionmentioning
confidence: 99%